UPACARA MENGRUMBANG PADA ETNIK PAKPAK DI DESA KECUPAK KECAMATAN PERGETTENG GETTENG SENGKUT KABUPATEN PAKPAK BHARAT - Manik, Jeremia; Damanik, Erond Litno (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2024)
The aim of this study was to find out the implementation process, the symbolic meaning contained and the views of the Pakpak ethnic community on the traditional ceremony of mengrumbang in Kecupak Village, Pergetteng Getteng Sengkut District, Pakpak Bharat Regency. The type of research used was qualitative with a descriptive approach centered in Kecupak Village, Pergetteng Getteng Sengkut District, Pakpak Bharat Regency. Data collection techniques used were observation, interviews and documentation studies where the collected data was analyzed through data reduction, data presentation and drawing conclusions. The results of the study revealed that the mengrumbang ceremony was a tradition related to the life cycle or rites passages, namely a form of payment of customary debt to the puang. The implementation process is carried out in three stages; (1) preparation (merkebbas), (2) implementation, and (3) closing. In the ceremony, the Pakpak ethnic has symbols that can be seen through the implementation process and the equipment or equipment used and has meaning contained through interpretations made and mutually agreed upon. Mengrumbang has an exclusive meaning, honor for the tribe (executor) which marks success and success.